Title VII’S Flight Beyond First Amendment Radar: A Yin-to-Yang Attenuation of “Speech” Incident to Discriminatory “Abuse” in the Workplace - Marks, John H. (Columbia Journal of Gender and Law, 1999)
Title VII of the Civil Rights Act of 1964 represents a comprehensive effort to remediate all vestiges of workplace discrimination against employees based on their race, color, religion, sex, or national origin. The focus of this article is on one branch of Title VII’s prohibition of sex discrimination in the workplace. That branch, commonly known as hostile-environment sexual harassment, is conceived of here as a critically important but mathematically imprecise line drawn by Title VII in the vast cosmos of workplace activity. The uncertain line delineates a threshold into a realm of sex-specific “abuse” that can undermine workplace equality just as seriously as outright denials of tangible job benefits on the basis of sex. Extreme incursions into the realm of sex-specific abuse are easy to identify. At the extreme, these abuse cases involve provocative patterns of verbal and physical assault directed at particular employees because of their sex. Typical of the extreme cases are individually targeted patterns of assaultive sexist insult (e.g., “dumb ass woman”), assaultive sexual propositions (e.g., “hey pussycat, come here and give me a whiff”), and assaultive touching, groping, and grabbing. Although not expressly forbidden by Title VII, severe or pervasive patterns of such activities clearly constitute a form of discriminatory abuse by implication contemplated by Title VII’s prohibition of sex discrimination in the workplace.